Lymphogranuloma venereum presenting with erythema nodosum. (December 2016) - Borsje, Annemiek; van der Reijden, Wil; Soetekouw, Robin
Lymphogranuloma venereum is a sexually transmitted infection caused by Chlamydia trachomatis serovar L1, L2 or L3. Anorectal infections in HIV-positive men who have sex with men comprise the majority of cases in the developed world. We present the case of a 30-year-old HIV-negative man with inguinal type lymphogranuloma venereum accompanied by erythema nodosum.